2017
DOI: 10.1016/j.paid.2017.04.017
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Triad and three types of jealousy: Its' relations among heterosexuals and homosexuals involved in a romantic relationship

Abstract: The current study examined the relations between the three Dark Triad (DT) traits and three types of jealousy, among both heterosexual and homosexual men and women involved in a romantic relationship (n = 439). It was hypothesized that the three DT traits would be related positively to those types of jealousy that have the potential to become delusional, that is anxious and preventive jealousy, but not to the relatively 'healthy' type of jealousy, that is reactive jealousy. In addition, differences were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 33 publications
(52 reference statements)
2
11
1
Order By: Relevance
“…As a consequence, this result combined with those from previous research reveals a somewhat mixed picture concerning the relationship between anxious jealousy and dark personality traits. Whereas two previous studies (Barelds et al, 2017(Barelds et al, , 2020 found relationships between anxious jealousy and the three Dark Triad traits in Dutch samples, in the present study's Dutch sample as well as the Curaçaon sample as described in Barelds et al (2020) no relationship between the Dark Triad traits and anxious jealousy was found. According to Barelds et al (2017) the relationships between the Dark Triad traits and anxious jealousy may be the result of high Dark Triad trait scorers' tendency toward short-term mating.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…As a consequence, this result combined with those from previous research reveals a somewhat mixed picture concerning the relationship between anxious jealousy and dark personality traits. Whereas two previous studies (Barelds et al, 2017(Barelds et al, , 2020 found relationships between anxious jealousy and the three Dark Triad traits in Dutch samples, in the present study's Dutch sample as well as the Curaçaon sample as described in Barelds et al (2020) no relationship between the Dark Triad traits and anxious jealousy was found. According to Barelds et al (2017) the relationships between the Dark Triad traits and anxious jealousy may be the result of high Dark Triad trait scorers' tendency toward short-term mating.…”
Section: Discussioncontrasting
confidence: 93%
“…The relationships between the Dark Triad traits and anxious and preventive jealousy may be the result of high Dark Triad trait scorers' tendency toward short-term mating. As a result, individuals with high scores on the Dark Triad traits are relatively likely to believe that their partner is also interested in extra-dyadic sex, and report stronger feelings of anxious and preventive jealousy as a consequence (Barelds et al, 2017).…”
Section: Dark Triadmentioning
confidence: 99%
“…Accumulating evidence has implicated the personality trait narcissism in relational dysfunction (e.g., Keller et al, 2014; Lamkin, Campbell, vanDellen, & Miller, 2015; Peterson & DeHart, 2014; Tortoriello, Hart, Richardson, & Tullett, 2017). For instance, narcissists 1 are both inclined to induce jealousy in partners (Campbell, Foster, & Finkel, 2002; Tortoriello et al, 2017) and to experience jealousy (Barelds, Dijkstra, Groothof, & Pastoor, 2017; Besser & Priel, 2010; Chin, Atkinson, Raheb, Harris, & Vernon, 2017). While work has explored the underlying motives of the former (Campbell et al, 2002; Tortoriello et al, 2017), research has yet to explore the underlying motives of the latter.…”
mentioning
confidence: 99%
“…Unlike reactive jealousy, both anxious and possessive jealousy can be "triggered in the absence of an extra dyadic rival" (Swami et al, 2012, p. 797). Possessive jealousy occurs when one attempts to prevent a situation from ever occurring (Barelds & Barelds-Dijkstra, 2007; Barelds, Dijkstra, Groothof, & Pastoor, 2017;Swami et al, 2012). An example of this could be an individual enacting surveillance or manipulation attempts toward their partner to make sure they do not spend time with specific people outside the relationship (Guerrero et al, 1995).…”
Section: Romantic Relationship Conflictsmentioning
confidence: 99%
“…An example of this could be an individual enacting surveillance or manipulation attempts toward their partner to make sure they do not spend time with specific people outside the relationship (Guerrero et al, 1995). Anxious jealousy occurs in anticipation of a situation (Barelds & Barelds-Dijkstra, 2007;Barelds et al, 2017;Swami et al, 2012) while reactive jealousy occurs after a situation has already taken place (Rotenberg, Shewchuk, & Kimberly, 2001). Anxious jealousy often lowers the relational quality, as rumination of hypothetical situations causes anxiety and distress, while reactive jealousy has been shown to increase relational quality because it is often viewed as showing love or care for one's partner (Barelsds & Barelds-Dijkstra, 2007).…”
Section: Romantic Relationship Conflictsmentioning
confidence: 99%